Effect of artificial substrate and supplementary feed on the production of Penaeus monodon (Fabricius) in extensive culture system - Combras, Nilda Uy (College of Fisheries, U. P. in the Visayas, 1991)
The study was conducted at the Brackishwater aquaculture Center, Institute of Aquaculture, U.P.V. College of Fisheries, Leganes, Iloilo to determine the effects of artificial substrate and supplementary feed on the growth, survival and production of Penaeus monodon in an extensive culture system. The experiment utilized twelve 200 sq. m. experimental brackishwater ponds. Four treatments were tested in a Randomized Complete Block design with three replicates. The treatments tested were : 1. Treatment I (Artificial Substrate Only). 2. Treatment II (Supplementary Feed Only), 3. Treatment III (Combination of Artificial substrate and Supplementary Feed) and 4. Treatment IV ( Control, No substrate and no Supplementary Feed). Treatment II (supplementary feed only) and Treatmeent III (combination of artificial substrate and supplementary feed) had significantly higher growth (P<0.05) over control. Treatment IV (no artificial substrate and no supplementary feed) and Treatment I (artificial substrate only) Treatment III (combination of artificial substrate and supplementary feed) gave the highest mean survival which was highly significantly higher (P<0.01) than Treatments I and IV. Treatment IV gave the lowest mean survival rate which was significantly lower than all other treatments. Mean production of Treatments II and III were significantly (P<0.01) higher than Treatments I and IV.